Control of a Modular Multilevel Converter for Fast Electric Vehicle Charging Applications - Espina-Gonzalez, E; Diaz-Diaz, M; Uriarte-Gonzalez, M; Ibaceta-Valenzuela, E (Institute of Electrical and Electronics Engineers Inc., 2022)
Modular Multilevel Converters are considered one of the most suitable technologies for High-Voltage Direct Current transmission. However, they have been recently proposed in additional applications such as electric vehicle charging, Solid-State Transformers, and motor drives. In this context, this paper presents the modeling and control of a Modular Multilevel Converter for isolated power transference applications. In this proposal, the converter is regulated to perform Medium-Voltage Low-Frequency Alternating Current conversion to Low-Voltage Medium-Frequency Alternating Current required for fast charging of Electric Vehicles. In addition, simulation results obtained with a 500 kW Modular Multilevel Converter Serie model using PLECS are presented to validate the proposed control and topology performance. © 2022 IEEE.